AIDS in Africans living in London. Issue 6 (December 1995) - O'Farrell, N; Lau, R; Yoganathan, K; Bradbeer, C S; Griffin, G E; Pozniak, A L
Abstract : OBJECTIVES–To investigate the presentation of HIV infection and AIDS amongst Africans diagnosed with AIDS living in London. METHODS–Identification of all AIDS cases of African origin attending four HIV specialist centres in South London–Guy's, King's, St George's and St Thomas' Hospitals–up to March 1994, by retrospective review of case notes of all HIV positive patients. RESULTS–Of 86 patients (53 women, 33 men) studied, 59 (69%) were from Uganda. The most frequent AIDS-defining diagnoses were: Pneumocystis carinii pneumonia (PCP) 21%, tuberculosis (TB) 20% (extrapulmonary TB 14%, pulmonary TB 6%), cerebral toxoplasmosis 14%, oesophageal candida 13%, cryptococcal meningitis 11%, wasting 6%, herpes simplex infection > 1 month 5%, Kaposi's sarcoma 5%, other 6%. Cytomegalovirus retinitis was diagnosed in one case. Late presentation was common; 70% were diagnosed HIV positive when admitted to hospital. The diagnosis of AIDS was coincident with a first positive HIV test result in 61%. The mean CD4 counts at both HIV and AIDS diagnoses were similar in both men and women: 87 x 10(6)/l and 74 x 10(6)/l in men and 99 x 10(6)/l and 93 x 10(6)/l in women respectively. Overall, TB 21 (24%) (extrapulmonary TB 12, pulmonary TB 9) was either the AIDS-defining diagnosis or was detected within three months of this event. Sixty-two per cent of TB cases were diagnosed within twelve months of entry to the UK compared to 34% of all other AIDS cases. The prevalence of STD was very low; genital herpes was the commonest STD: 17% of the women, 9% men; 28% of the men and 11% of the women tested had a positive TPHA test. In cases known to be HIV-positive prior to an AIDS diagnosis, 41% took prophylaxis for PCP and 45% had taken zidovudine (ZDV). Forty two of the study participants had 89 children: 59 of these children had mothers in the study. Overall, 37 (42%) of the children had lost at least one parent at the time of data assessment. CONCLUSIONS–PCP and TB were the most common initial AIDS-defining diagnoses. The majority of TB cases were diagnosed within 12 months of entry to the UK. An AIDS-defining diagnosis was the first manifestation of HIV-related illness in the majority of patients. Because of late presentation to medical services, access to treatments for HIV infection and prophylaxis against opportunistic infections was limited. Extending the role of clinics and staff into the community might facilitate both earlier presentation and access to services. Future provision of local services will need to be sensitive to the requirements of individuals from different cultures and backgrounds.